Prostituição: vozes que ecoam, sereias que (en)cantam. - Ferraça, Mirielly (2013)
Taking as a basis interviews made with four female escorts , prostitutes, under the approval of the Ethics in Research Committee (Comite de Ética em Pesquisa CEP) of the Western Parana State University UNIOESTE, this research aims to analyze some Discursive Sequences (SD), according to the French Stream of Discourse Analysis. Thus, by verifying, in the discourse repetition, the discursive memory presence, that contributes to crystallize some meaning effects about prostitution activity, it was tried to understand which meanings echo over the selected SDs. The analysis chapters were organized following some general themes in which the discourses meet and repeat themselves. In the first, it is put under discussion the entrance door of that activity, evidencing in the linguistic materiality, the pointed causes that incited them to start prostituting themselves. Excuses are presented by the interviewees that direct the guilty of being there (doing that activity) to the other . Nonetheless, along the thread of the discourse, it is noticed that the justifications do not redeem them, because, if the explanations were enough, those women would not need to hide from family, children, and friends what they do to make a living, would not need to hide themselves in the night shadows. It is understood that those woman judge according to the same moral pattern whereby they are judged. Then, in the following parts of the work, the objective is to find and contemplate the statements (utterances, stretches of text) where they appear as moralists and followers of the established moral about what is acceptable and right . In order to conclude the analysis, it is dealt with the SDs which refer to the way out from the Siren s Harbour (fictional name used to refer to the place where they work, the brothel), where the research was made. The alternatives pointed are shared between them: another profession, education, and marriage. They pursue exits that might redeem themselves from the way they live, making them subjects that are part of the social dynamics, with acts agreeing to what is taken as correct and expected of a woman. In the research, it is noticed that the crystallized discourse about prostitution still commands and it is reflected in the speech of the interviewees, showing a contradictory discourse of women living on the in-between: they are neither only on the margins (because they are also mothers, daughters, ex-wives), nor fully taking part of the social dynamics accepted as correct.